A Comparison of Biophysical Conditions Between Sundanese Migrant and Non-Migrant Pekarangans in Indonesia - Ali, Muhammad Saddam; Arifin, Hadi Susilo; Arifin, Nurhayati; Astawan, Made (Frontiers in Environmental Science, 2022)
Pekarangan is a typical Indonesian home garden. This paper aimed to look at biophysical conditions of pekarangan between Sundanese migrants and non-migrants. A total of 40 pekarangans in Selajambe and Ciomas Rahayu villages, West Java were chosen as representative locations for the Sundanese non-migrant population (native Sundanese) and 40 pekarangans in Tegal Yoso and Tanjung Kesuma villages, Lampung, were chosen as representatives of the Sundanese migrant population. Research has been carried out in the period 2019 and 2021. To measure the biophysical condition of pekarangan, we analyzed pekarangan area, pekarangan size, number of species and individual of pekarangan plants, vertical diversity and horizontal diversity of plants, and the relationship between pekarangan area and number of species and individual plants. The results showed that the difference in conditions of pekarangan were indicated by the difference in area and size, but not by the diversity of the plants. Both types of pekarangans have the same level of diversity as indicated by the number of individual plants that are almost the same in number per 100 m2. In addition, a strong and positive correlation (0.69 - 0.88) between the area of pekarangan and the number of individual plants indicated that the small - medium size or large pekarangan sizes had almost the same diversity of plants. The difference lied in the type of plant that is cultivated. Migrant pekarangan are dominant in cultivating food crops, while non-migrant pekarangan are dominant in cultivating ornamental plants. The selection of plants that have important and valuable functions can be a solution in maintaining the area of the pekarangan. Choosing plants with a variety of functions can be an option for a small-medium pekarangan size. To improve the biophysical condition of pekarangan was also inseparable from the involvement of economic, social, and cultural aspects in pekarangan.